Kingdom of Lesotho : Staff Report for the 2005 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
The Kingdom of Lesotho's 2005 Article IV Consultation reports that the government's fiscal position and the external current account have improved markedly. The authorities are preparing an action plan, in collaboration with development partners, to improve the business climate. Critical measures aim to increase labor productivity through training, reduce domestic costs for the private sector by addressing infrastructure bottlenecks, remove regulatory and administrative impediments, improve access to financial services, and promote product and export market diversification.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet